Guest Editorial: Community Information Services - Venkatappaiah, V. (DESIDOC Journal of Library & Information Technology, 2003)
Community services have been existing in India since the inception of Gram Panchayats, but the term community Information Services (CIS) is of recent origin,and may have its roots in the west. it has been emerging as a fact of public libraray system in the developing countries, with Britain and America taking the leads in this regard. http://dx.doi.org/10.14429/dbit.19.1.3453